URGENSI PEMBANGUNAN PEDESAAN DALAM MEWUJUDKAN KETAHANAN PANGAN NASIONAL (URGENCY OF RURAL DEVELOPMENT FOR REACHING NATIONAL FOOD SECURITY) - Hariadi, Sunarru Samsi (Jurnal Ilmu-Ilmu Pertanian, 2008)
Rural development is very important for reaching national food security. The goal of rural development is not only for increasing agricultural productivity, but also multysectoral development. Multi-sectoral development which is synergic among subsectors will increase peoples income, increase home industry sector in rural areas, will support agriculture and absorption agricultural laborers, also increase peoples welfare, so it will reach food security. Food security is not only enough food for every household, but also institutionalized custom of household consumption so that people do not have to eat rice as main food everyday, but they can consume other kinds of food as main food, for instance cassava, corn, sago, etc, that can be locally provided (not imported).